Evolutionary multi-move path-relinking for transmission network expansion planning - Rahmani, M. [UNESP]; Rashidinejad, M.; Carreno, E. M. [UNESP]; Romero, R. A. [UNESP]; IEEE (Ieee, 2010)
This paper presents the application of a new metaheuristic algorithm to solve the transmission expansion planning problem. A simple heuristic, using a relaxed network model associated with cost perturbation, is applied to generate a set of high quality initial solutions with different topologies. The population is evolved using a multi-move path-relinking with the objective of finding minimum investment cost for the transmission expansion planning problem employing the DC representation. The algorithm is tested on the southern Brazilian system, obtaining the optimal solution for the system with better performance than similar metaheuristics algorithms applied to the same problem.
Keywords: Transmission expansion planning; Construction phase; Multi-move path-relinking; GRASP